English Use in The Advertisement Texts of Hotel 99 Jember - Agung Tri Wahyuningsih; Wisasongko Wisasongko; Eka Mirwadiva (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2019)
Advertisement is one of short functional texts used to gain customers’ attention. Its visual portray determines whether this persuasive passage will successfully grab the interest of readers and direct them to finally use the product or ignore it. Batchia and Ritchie (2006: 19) proposes that “English is important vehicle for global advertisement”. Additionally, Piller (2003: 17) states that “English is the most commonly used language in advertising especially in non-English speaking countries or multilingual country.” These two intriguing ideas of using English in advertisement direct the advertiser of Hotel 99 Jember to insert some English Code. Through its official Instagram (hotel.99.jember) the advertiser publicly publishes some postings about the hotel. Those postings attract the researchers’ curiosity to know why English is existing there and what the benefits of English insertions to the hotel are. Laying on Zohreh and Monireh’s finding (2013: 87), this investigation is conducted to match the four influencing reasons (gaining attention, persuasion, prestige, and technology) affecting the advertiser to put English in the advertisement texts. Interview is chosen as the way to investigate the advertiser’s reasons. Further, customers’ responses are also the case examined in this research. By having customers’ responses, it is worth to know whether English use effectively influences them to choose the hotel or not. Finally, this research is not only beneficial to the researchers to deeply study about English use but also for the hotel to thoroughly know the effect of their advertisement texts in Instagram.